Facile synthesis of silver nanoparticles using leaf extract of Hyptis suaveolens (L.) Poit for environmental and biomedical applications. Issue 1 (March 2020) - Lateef, A; Oladejo, S M; Akinola, P O; Aina, D A; Beukes, L S; Folarin, B I; Gueguim-Kana, E B
Abstract: Aqueous leaf extract of Hyptis suaveolens was investigated to synthesize silver nanoparticles (Hs-AgNPs). Biomolecules such as phenolics, proteins, carbohydrates and esters facilitated bioformation of Hs-AgNPs with ƛmax at 420 nm. The nearly spherical Hs-AgNPs were polydispersed and sized 29.19-52.27 nm with yield of 85.8 %. Hs-AgNPs showed potent inhibition of 75.22-100 % against multidrug resistant bacteria, and fungal growth inhibition of 73.33-100 %. Hs-AgNPs scavenged DPPH and H2 O2 by 77.75-83.19, and 54.21-70.11 % respectively. It also effectively inhibited coagulation of blood. The study established the nanobiotechnological importance of H. suaveolens, with bioformation of AgNPs that have potent activities for environmental and biomedical applications.